PENGARUH INOVASI, POSITIONING PRODUK, DAN ELECTRONIC WORD OF MOUTH TEHADAP MINAT BELI SEPEDA LISTRIK (STUDI KASUS KONSUMEN SEPEDA LISTRIK DI MAGETAN) - Fauzi, Rizal Ula Ananta; Kadi, Dian Citaningtyas Ari; Firdaos, Shofwan (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the effect of innovation, product positioning, and electronic word of mouth (eWOM) on buying interest in electric bicycles in Magetan Regency. The study used a quantitative approach with a survey method involving 384 respondents. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that product positioning and eWOM had a positive and significant influence on the purchase intention of electric bicycles, while innovation did not show a positive and insignificant influence. Good product positioning creates a strong perception in the minds of consumers, and eWOM, through online reviews and recommendations, increases consumer confidence in electric bicycles. Although product innovation was found to have no direct influence, this study highlights the importance of developing other marketing aspects to drive purchase intention.